The urokinase plasminogen activator receptor (uPAR) controls macrophage phagocytosis in intestinal inflammation. Issue 4 (21st May 2014) - Genua, Marco; D'Alessio, Silvia; Cibella, Javier; Gandelli, Alessandro; Sala, Emanuela; Correale, Carmen; Spinelli, Antonino; Arena, Vincenzo; Malesci, Alberto; Rutella, Sergio; Ploplis, Victoria A; Vetrano, Stefania; et al.
Abstract : Objective: Inflammation plays crucial roles in the pathogenesis of several chronic inflammatory disorders, including Crohn's disease (CD) and UC, the two major forms of IBD. The urokinase plasminogen activator receptor (uPAR) exerts pleiotropic functions over the course of both physiological and pathological processes. uPAR not only has a key role in fibrinolysis but also modulates the development of protective immunity. Additionally, uPAR supports extracellular matrix degradation and regulates cell migration, adhesion and proliferation, thus influencing the development of inflammatory and immune responses. This study aimed to evaluate the role of uPAR in the pathogenesis of IBD. Design: The functional role of uPAR was assessed in established experimental models of colitis. uPAR deficiency effects on cytokine release, polarisation and bacterial phagocytosis were analysed in colonic macrophages. uPAR expression was analysed in surgical specimens collected from normal subjects and patients with IBD. Results: In mice, uPAR expression is positively regulated as colitis progresses. uPAR-KO mice displayed severe inflammation compared with wild-type littermates, as indicated by clinical assessment, endoscopy and colon histology. The absence of uPAR led to an increased production of inflammatory cytokines by macrophages that showed an M1 polarisation and impaired phagocytosis. In human IBD, CD68 + macrophages derived from the inflamed mucosa expressed low levels of uPAR. Conclusions: These findings point to uPAR as an essential component of intestinal macrophage functions and unravel a new potential target to control mucosal inflammation in IBD.